2022
DOI: 10.1007/s00213-022-06069-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of docosanyl ferulate, a constituent of Withania somnifera, on ethanol- and morphine-elicited conditioned place preference and ERK phosphorylation in the accumbens shell of CD1 mice

Abstract: Background Docosanyl ferulate (DF) is a behaviourally active GABAA receptor complex (GABAAR) agonist, recently isolated from the standardized methanolic extract of Withania somnifera Dunal (WSE) root. Previous studies have shown that WSE prevents both ethanol- and morphine-dependent acquisition and expression of conditioned place preference (CPP) and stimulation of dopamine release in the nucleus accumbens shell (AcbSh). Aims The study aimed at determining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 62 publications
3
5
0
Order By: Relevance
“…Most importantly, our results may suggest that new possible directions in the development of the therapeutic perspectives of WS extracts should take advantage from the use of alkaloid-enriched fractions, since a favorable efficacy/tolerability profile could be observed in vitro when WSA is compared to conventional WSE and WSW in RAW 264.7 macrophages. This finding is consistent with recent studies showing that WS components diverse from withanolides have relevant pharmacological activity, thus calling for future in vitro and in vivo studies on WS [29][30][31].…”
Section: Results and Conclusionsupporting
confidence: 92%
“…Most importantly, our results may suggest that new possible directions in the development of the therapeutic perspectives of WS extracts should take advantage from the use of alkaloid-enriched fractions, since a favorable efficacy/tolerability profile could be observed in vitro when WSA is compared to conventional WSE and WSW in RAW 264.7 macrophages. This finding is consistent with recent studies showing that WS components diverse from withanolides have relevant pharmacological activity, thus calling for future in vitro and in vivo studies on WS [29][30][31].…”
Section: Results and Conclusionsupporting
confidence: 92%
“…Similar to what observed in morphine-treated mice, WSE administration reduced the motivation for alcohol drinking, the alcohol deprivation effect, and the reinstatement of alcohol-seeking behaviour evaluated with the operant self-administration paradigm [23]. Moreover, WSE impaired the acquisition and expression of alcohol-elicited place conditioning as well as the phosphorylation of the extracellular signal-regulated kinase in the shell of the nucleus accumbens of mice [9,24], and prevented both morphine-and alcohol-elicited mesolimbic increases in dopamine transmission in rats [7].…”
Section: Introductionsupporting
confidence: 70%
“…Interestingly, rodent studies from our group have previously demonstrated the efficacy of WSE in contrasting alterations associated not only with neurological disorders [1][2][3][4][5][6], but also with the exposure to addictive drugs, such as morphine and alcohol. Consistent with this, rodents treated with WSE displayed a reduction in the behavioral and neurochemical alterations induced by morphine or alcohol administration [7][8][9]. These findings indicate that WSE positively affects brain function and led us to hypothesize that it could also contrast the detrimental effects elicited in the brain by amphetamine-related drugs endowed with neurotoxic and neuroinflammatory properties.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations